2011
DOI: 10.1186/1472-6815-11-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiological findings in patients undergoing revision endoscopic sinus surgery: a retrospective case series study

Abstract: BackgroundFunctional endoscopic sinus surgery (FESS) is now a well-established strategy for the treatment of chronic rhinosinusitis which has not responded to medical treatment. There is a wide variation in the practice of FESS by various surgeons within the UK and in other countries.ObjectivesTo identify anatomic factors that may predispose to persistent or recurrent disease in patients undergoing revision FESS.MethodsRetrospective review of axial and coronal CT scans of patients undergoing revision FESS betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
60
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 18 publications
11
60
2
Order By: Relevance
“…We believe that the study provided a realistic depiction of such referrals to tertiary centers and echoed radiologic findings of U.K. revision ESS cases identified by Kahlil et al 30 Of these, the highest rates of failure demonstrated here related to those steps that may be considered to be the simplest to perform, e.g. , uncinectomy and antrostomy.…”
Section: Discussionsupporting
confidence: 80%
“…We believe that the study provided a realistic depiction of such referrals to tertiary centers and echoed radiologic findings of U.K. revision ESS cases identified by Kahlil et al 30 Of these, the highest rates of failure demonstrated here related to those steps that may be considered to be the simplest to perform, e.g. , uncinectomy and antrostomy.…”
Section: Discussionsupporting
confidence: 80%
“…In up to 7% of cases, a lateral synechia can arise in the area of the medial orbital wall [265], [289] (Figure 3 (Fig. 3)).…”
Section: “Minor” Complicationsmentioning
confidence: 99%
“…Endoscopic sinus surgery (ESS) is now a well-established strategy for the treatment of chronic rhinosinusitis that has not responded to medical treatment [1]. Increased visualization, superior cosmesis, and decreased postoperative recovery time justify the use of ESS in almost all diseases of the paranasal sinuses [2].…”
Section: Introductionmentioning
confidence: 99%